2018
DOI: 10.1093/ofid/ofy050
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Torque Teno Virus and Epstein-Barr Virus Is of Limited Value for Predicting the Net State of Immunosuppression After Lung Transplantation

Abstract: BackgroundMajor hurdles for survival after lung transplantation are rejections and infectious complications. Adequate methods for monitoring immune suppression status are lacking. Here, we evaluated quantification of torque teno virus (TTV) and Epstein-Barr virus (EBV) as biomarkers for defining the net state of immunosuppression in lung-transplanted patients.MethodsThis prospective single-center study included 98 patients followed for 2 years after transplantation. Bacterial infections, fungal infections, vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 45 publications
1
38
0
Order By: Relevance
“…In line with previous reports, TTV was detected frequently in donors and recipients, and levels were shown to increase in transplant recipients, which is consistent with prior reports on transplant patients receiving immunosuppressive treatment [34][35][36][37]. Due to low read numbers, it was not possible to assess whether TTV was also transmitted from positive donors to recipients.…”
Section: Parameters Of Renal Function and Jc Polyomavirus Infectionsupporting
confidence: 88%
“…In line with previous reports, TTV was detected frequently in donors and recipients, and levels were shown to increase in transplant recipients, which is consistent with prior reports on transplant patients receiving immunosuppressive treatment [34][35][36][37]. Due to low read numbers, it was not possible to assess whether TTV was also transmitted from positive donors to recipients.…”
Section: Parameters Of Renal Function and Jc Polyomavirus Infectionsupporting
confidence: 88%
“…The replication kinetics observed in our cohort was similar to that previously reported in LT recipients, with a rapid increase in viral load from days 7 to 30, which was followed by a less pronounced slope thereafter, to peak beyond month 3 in most patients. 15,44 It should be noted that the alphatorquevirus doubling time was higher during the first posttransplant week than in the subsequent period until day 30, pointing to a certain delay in the triggering effect of iatrogenic immunosuppression on viral replication and shaping a sigmoid-like curve, which has also been observed after LT. 15 Recent studies have reported an association between low or undetectable alphatorquevirus viremia and an increased risk of graft rejection after lung, 24 kidney, 23 and liver transplantation. 22 Similarly to our experience, data from the Swiss Transplantation Cohort Study showed that 1-year cumulative incidence of rejection among liver transplant recipients with undetectable TTV DNA loads at transplantation were significantly higher than in patients with detectable titers.…”
Section: Discussionmentioning
confidence: 84%
“…15,44 It should be noted that the alphatorquevirus dou- Competitiveness. 15,44 It should be noted that the alphatorquevirus dou- Competitiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Wohlfarth et al, in turn, showed a direct link between TTV DNA and CMV infection, as well as a linear correlation between the DNA of both viruses . In the context of solid organ transplantation, a direct association between TTV and CMV infection has been reported in kidney transplantation, whereas a report on lung recipients found no relationship . These conflicting results may be partially explained by the inherent differences between the distinct types of organ transplantation, as well as the various types of immunosuppressive regimens used (and thus the different immunosuppressive burden).…”
Section: Discussionmentioning
confidence: 99%